Generation of alginate encapsules to load nanoparticles for nir induced release for 5-fu - Kashthuri Thirumurugan (2014)
The aim of this work is to generate monodispersed alginate microspheres with desired specifications, especially in terms of size and shape. The focus of the experimental procedure will be, not only on the process of generating and collecting the droplets but also to modify, optimize and standardize methods and parameters involved for controlled microdroplet production. The purpose of generating these microspheres is to bring in the advantages of controlled processing techniques in microfluidics into the field of oncology. Although based on the overall methodology that has been previously established and verified, the experimental protocol aims to ‘fine-tune’ the minor aspects of droplet generation concept. In this work, tests have been performed in an attempt to isolate the effect of one parameter on the generation and properties of the spheres without influence from other parameters. Such an exercise will be useful in understanding the very fundamentals and physics of microfluidics and to contribute yet another improvised option for producing efficient cancer drug carrier systems.